Pengaruh Aktivasi Termal Abu Dasar Batubara terhadap Kinerja Adsorpsi dalam Peningkatan Sifat Fisik Pelumas Bekas - Randy Kurniawan; Darrel Parulian Cleverson Aritonang; Dino Nata Hidayat; Raihan Ramadhan; Asri Damertine Girsang; Devano Ramadhan; Rezky Tri Yunanda; Glory Florensa Br Siregar; Rikki Martin Nababan; Ummi Kulsum Hidayati (Universitas Muhammadiyah Metro, 2026)
Used lubricating oil contains degradation products and contaminants that may cause environmental pollution if improperly disposed of. This study investigated the utilization of coal bottom ash as an adsorbent for used lubricating oil purification and evaluated the effect of thermal activation on its adsorption performance. Bottom ash was purified using 2 M H₂SO₄ and subsequently thermally activated at 650°C for 3 h with NaOH assistance. The chemical composition of the adsorbent was analyzed using X-ray Fluorescence (XRF), while adsorption performance was evaluated through density, kinematic viscosity, and flash point measurements of the treated oil. XRF results showed that the purification process reduced Ca content from 22.36 wt.% to 10.44 wt.% and Fe content from 29.19 wt.% to 20.61 wt.% while preserving the major silica and alumina components. The thermally activated bottom ash exhibited better adsorption performance than the non-activated adsorbent, resulting in higher density and viscosity values of the treated oil. These findings demonstrate that thermal activation improves the adsorption capability of bottom ash, indicating its potential as a low-cost and environmentally friendly adsorbent for used lubricating oil purification.